10 year anniversary of the Journal APSTRACT: The history of an open access journal - Kovács, Krisztián; Csapóné Riskó , Tünde; Csapó, Zsolt; Nábrádi , András (Applied Studies in Agribusiness and Commerce, 2017)
The idea initiating the birth of the journal APSTRACT was initiated by András Nábrádi, during a 2005 AGRIMBA1 executive board meeting held in Aberdeen, UK. AGRIMBA is an open international network of academics and professionals from universities and related institutions dealing with education and research in agribusiness (Csapó et al., 2010). Currently, the Network is especially active in Central and Eastern Europe (Heijman, 2015). The main objective of the Network is to set standards based on best practices for programmes it oversees and to accredit them on the basis of these standards. The International MBA Network was established in 1995, by founding members from Wageningen University, Scottish Agricultural College, the Czech University of Life Sciences in Prague, Warsaw Agricultural University, University College Cork and the University of Wolverhampton. Between 2000 and 2009, the following universities joined the Network: Humboldt University Berlin, the University of Debrecen, Arkansas State University, the Agricultural University of Ukraine, the Timiryazev Academy in Moscow, the University of Belgrade and the University of Zagreb (Heijman, 2015). The Universities of Belgorod (Russia) and Kazan (Russia) has also joined the network last year. JEL code: A10